(untitled) (Research, Society and Development, 2022)
Objective: To describe the challenges of teaching in remote education through a literature review. Methods: This is an exploratory and descriptive literature review of population-based studies from 2016 to 2021. PubMed, Scielo and VHL electronic databases were used; search strategy applied, selection performed, data extraction of studies and categorization of central ideas into thematic categories. Results: Of the 1,588 retrieved studies, 18 articles with varied methodological approaches were included after eligibility selection. The following challenges were most frequently mentioned from the perspective of health professors in remote teaching: competencies and development of new pedagogical skills; organizational infrastructure and logistics; interpersonal relationships and mental health; and concerns related to the teaching of practical skills. Conclusion: The pandemic scenario caused by the new coronavirus has promoted the intensification of remote teaching. In the health context, this teaching modality requires adaptations in the way content is administered, as well as greater technical, professional, and psychosocial support to teachers.